Microwave-assisted synthesis of anhydrous lanthanide-based coordination polymers built upon benzene-1, 2, 4, 5-tetracarboxylic acid. (1st August 2021) - Amiaud, Thibault; Stephant, Nicolas; Dessapt, Rémi; Serier-Brault, Hélène
Graphical abstract: A series of trivalent lanthanide and group 3 metal coordination polymers with pyromellitic acid has been synthesized and structurally characterized. Lacking any solvent molecules, their exhibit a high thermal stability up to 400–500°C under air. Moreover, the compounds are highly stable in water in a wide pH range. The Eu counterpart present high luminescence properties with quantum yield of 25%. Abstract: A series of trivalent lanthanide and group 3 metal coordination polymers with pyromellitic acid [M(Hbtec)]n (M = Eu, Dy, Sm, Nd, Ce, Er, Y) has been synthesized and structurally characterized. Contrary to most of coordination polymers, the reported compounds do not present any crystallized solvent molecules, and consequently they are thermally stable until 400–500 °C. Moreover, they also exhibit good stability in water on a wide pH range. Compounds were synthesized by hydrothermal route with conventional heating but also with microwave-assisted heating, allowing to noticeably reduce the synthesis time to 1 h max. Efforts have been done to obtain nanoparticles with this strategy. Finally, the luminescence properties of the lanthanide counterparts emitting in the visible range (Dy, Sm, Eu) were thoroughly investigated, and the Eu compound exhibit good quantum yield.